Adolescent but not adult-born neurons are critical for susceptibility to chronic social defeat - Kirshenbaum, Greer S.; Lieberman, Sophie R.; Briner, Tamara J.; Leonardo, E. David; Dranovsky, Alex (Frontiers in Behavioral Neuroscience, 2014)
Recent evidence implicates adult hippocampal neurogenesis in regulating behavioral and physiologic responses to stress. Hippocampal neurogenesis occurs across the lifespan, however the rate of cell birth is up to 300% higher in adolescent mice compared to adults. Adolescence is a sensitive period in development where emotional circuitry and stress reactivity undergo plasticity establishing life-long set points. Therefore neurogenesis occurring during adolescence may be particularly important for emotional behavior. However, little is known about the function of hippocampal neurons born during adolescence. In order to assess the contribution of neurons born in adolescence to the adult stress response and depression-related behavior, we transiently reduced cell proliferation either during adolescence, or during adulthood in GFAP-Tk mice. We found that the intervention in adolescence did not change baseline behavioral responses in the forced swim test, sucrose preference test or social affiliation test, and did not change corticosterone responses to an acute stressor. However following chronic social defeat, adult mice with reduced adolescent neurogenesis showed a resilient phenotype. A similar transient reduction in adult neurogenesis did not affect depression-like behaviors or stress induced corticosterone. Our study demonstrates that hippocampal neurons born during adolescence, but not in adulthood are important to confer susceptibility to chronic social defeat.